Optimum Phase Number for Multiphase PWM Inverters - Anwar Muqorobin; Pekik Argo Dahono; Agus Purwadi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
This paper investigates the optimum phase number for multiphase PWM inverters. The input current ripple is used as  a  performance  indicator.  Analysis results  show  that  phase number more than nine cannot provide significant input current ripple reduction. Experimental results are included in this paper to show the validity of the proposed analysis method.